2020
DOI: 10.3889/oamjms.2020.5252
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Children with Cancer: National Surveys of Practices and Perceptions in Morocco

Abstract: AIM: The aim of the study was to improve the quality of pain management in Moroccan pediatric oncology units, the Moroccan Society of Paediatric Haematology/Oncology initiated a national quality improvement project in 2014 with the support of the Lalla Salma Foundation for Prevention and Treatment of Cancer. METHODS: To assess the current situation of pain management in Moroccan pediatric oncology patients, two cross-sectional surveys were conducted, involving patient/parental proxies and health-care pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
1
0
1
Order By: Relevance
“…Relacionamos esses dois erros conceituais com o fato de que, quando questionados em relação a ter realizado algum treinamento em relação à avaliação e controle de dor, recebemos 100% de respostas negativas pelos auxiliares e técnicos de enfermagem, contra 40% dos médicos e 60% das enfermeiras, que referiram já terem feito capacitações específicas sobre o tema. Em estudo realizado no Marrocos, foi igualmente constatado que a grande maioria dos profissionais de saúde (74%) não tinha formação específica em gestão de dor, e isso tornou-se obstáculo ao bom tratamento da dor dos pacientes (KHOUBILA et al, 2020).…”
Section: Discussão Sobre Os Resultados Descritivosunclassified
“…Relacionamos esses dois erros conceituais com o fato de que, quando questionados em relação a ter realizado algum treinamento em relação à avaliação e controle de dor, recebemos 100% de respostas negativas pelos auxiliares e técnicos de enfermagem, contra 40% dos médicos e 60% das enfermeiras, que referiram já terem feito capacitações específicas sobre o tema. Em estudo realizado no Marrocos, foi igualmente constatado que a grande maioria dos profissionais de saúde (74%) não tinha formação específica em gestão de dor, e isso tornou-se obstáculo ao bom tratamento da dor dos pacientes (KHOUBILA et al, 2020).…”
Section: Discussão Sobre Os Resultados Descritivosunclassified
“…However, patients with burn injuries and family caregivers have little information about pain management (Heydarikhayat et al, 2018). In a similar cross-sectional survey in Morocco, most family caregivers requested additional information regarding pain management (Khoubila et al, 2020). The last finding of this study found that caregivers in the experimental group were more likely to return the patient to the burn clinic.…”
Section: Discussionmentioning
confidence: 99%